"Effectiveness of Punishment for Perpetrators of Domestic Violence against Children: Study of Decision Number 18/Pid.Sus/2017/PN Bek" - Khoiriah, Nur; Muslim, Ikhwanul; Sunariyo, Sunariyo (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
This research discusses the long-term impact of domestic violence (DV) on children, both physically, psychologically, and socially. The purpose of the research is to examine the punishment of perpetrators of domestic violence, analyze the legal process, and evaluate the judge's consideration in Decision Number 18/Pid.Sus/2017/PN Bek. By using a case study-based normative juridical method and regulatory analysis, this study found that criminalization includes physical, psychological, sexual violence, and neglect, with penalties tailored to the level of offense. In the verdict, the defendant was only sentenced to eight months' imprisonment from an initial sentence of one year, with consideration of factors that were more mitigating for the perpetrator than the impact experienced by the victim. The leniency of the sentence was attributed to the defendant's lack of a criminal record, even though the victim suffered severe physical and mental harm. Therefore, this research emphasizes the need for stricter legal policies and the application of more severe criminal sanctions to strengthen child protection in domestic violence cases.